Analisis Implementasi Sistem Informasi Administrasi Kependudukan ( SIAK ) Studi kasus Dinas Kependudukan dan Pencatatan Sipil lampung Utara - Rahmawati, Anisa Dwi; Handayani, Agustuti (JURNAL SOSIAL DAN HUMANIS SAINS, 2022)
The Population Administration Information System (SIAK) is an information system that utilizes information and communication technology to facilitate the management of population administration information at the level of organizers and implementing agencies as a single unit. The purpose of this study is to describe how the Implementation of the Population Administration Information System (SIAK) case study North Lampung Population and Civil Registration Service as well as supporting and hindering aspects of the Implementation of the Population Administration Information System (SIAK) at the North Lampung Population and Civil Registration Service. The research method uses a descriptive qualitative research method. The results showed that the implementation of the Population Administration Information System (SIAK) case study of the Department of Population and Civil Registration of North Lampung was running well in processing population administration data. The supporting factor is the existence of an integrated regional service unit (UPTD) in each sub-district that helps serve population administration, information is online. The inhibiting factor is that the community is not optimal in using the internet, the public does not understand the importance of population documents, SIAK development facilities and employees who have the ability according to their fields.